مساهمة النسب المالية المشتقة من التدفقات النقدية ونموذج شيرود في التنبؤ بالفشل المالي في المؤسسة الاقتصادية-دراسة حالة-مؤسسات فندقية(2015-2018) - الساسي, هلال; بوكرديد, عبد القادر (جامعة الوادي - University of Eloued, 2021)
: The study aims to analyze the financial position of the economic enterprise through the financial ratios derived from the cash flow schedule and approved models for predicting failure. To achieve this, my hot El awrassi -Merhaba (2015-2018) was chosen to see how efficient and effective each one is, as well as to predict the failure that is one of the impediments to their economic viability. It concluded that Elawrassi hotel achieved positive results during the period, as represented by the positive accounting result of the four years, while Merhaba hotel was arranged according to the Sherrod model in category IV, which is threatened by financial failure in the future. The repeated loss over the four years confirms this and an indication of the financial fragility of this institution .abstract is a brief, comprehensive summary of the contents of the article).
The Contribution of Cash Flows Ratios and the Sherrod Model in Predicting Financial Failure -Case Study -Hotel Enterprises
مقال
Keywords: تسيير الخزينة ; نسب مالية ; توازن مالي ; نموذج Sherrod ; فشل مالي.; Management of the treasury ; financial ratios ; financial balance ; Sherrod model ; financial failure